2023
DOI: 10.3390/jcm12062234
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Association between Thyroid Diseases and Colorectal Cancer

Abstract: Benign and malignant thyroid diseases (TDs) have been associated with the occurrence of extrathyroidal malignancies (EMs), including colorectal cancers (CRCs). Such associations have generated a major interest, as their characterization may provide useful clues regarding diseases’ etiology and/or progression, with the possible identification of shared congenital and environmental elements. On the other hand, elucidation of the underlying molecular mechanism(s) could lead to an improved and tailored clinical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…For instance, L'Heureux conducted a case-control study in Taiwan including 69,713 CRC patients and 69,713 controls. It showed a 22% lower risk of CRC in people with hypothyroidism with an adjusted OR of 0.78 [30,31] . Another study by Mondul et al observed that people with hypothyroidism were at decreased risk of prostate cancer compared to men with normal thyroid function [32,33] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, L'Heureux conducted a case-control study in Taiwan including 69,713 CRC patients and 69,713 controls. It showed a 22% lower risk of CRC in people with hypothyroidism with an adjusted OR of 0.78 [30,31] . Another study by Mondul et al observed that people with hypothyroidism were at decreased risk of prostate cancer compared to men with normal thyroid function [32,33] .…”
Section: Discussionmentioning
confidence: 97%
“…Another study by Mondul et al observed that people with hypothyroidism were at decreased risk of prostate cancer compared to men with normal thyroid function [32,33] . However, there were studies that conflicted with the association [10,30,34] .…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested that breast and thyroid cancers are clinically related to estrogen, a direct cause remains unknown [ 22 ]. Instead, estrogen influences cellular functions by binding to nuclear receptors identified as estrogen receptors alpha and beta (ERα and Erβ, respectively) [ 23 ]. The expression of ERs, particularly ERα is involved in the development of thyroid cancer in patients with breast cancer [ 5 ].…”
Section: Discussionmentioning
confidence: 99%